Employees Awareness and Practices of Saving on the Financial Institutions in Oromia Region, Ethiopia - Behailu Cufa; Arga Shure; Tarik Kechema (MANDALIKA : Journal of Social Science, 2026)
Saving is an economic term used to a proper utilization of resources that represents one of the most predictable determinants of successful personal and economic development. The purpose of this study is to identify employees’ awareness about saving and the major problems of employees’ practices of saving on the FIs in Oromia Region, Ethiopia. This study use quantitative research approach, particularly survey design. The result indicates that (107)47.80% employees had no saving experience and (118)52.20% of the respondents have been involved in saving part of their income. The most important covariates identified in the descriptive statistical analysis indicated that employer job position, gender, age, marital status, level of education, religion, ethnicity, monthly income, housing condition and family size were associated with saving practice in the study area. The effect of SA (Saving awareness) which is (Beta=-0.594076) significant (P, 0.05) is and its coefficient is negative indicating that the greater the saving awareness the lower the value of financial institutions in Ethiopia. The SA is highly lower the value of financial institutions. This result also makes sense, because both the theoretical and empirical evidences support that too. The effect of saving practice value is also (SP, Beta = - 0.836180) significant (p, 0.05) and as watched it is negative which indicates that the one unit increase in saving practice leads in- 0.836180 decrease in saving practice value on FIs. Finally, the variables like house hold composition, family health condition, impact of the financial crisis, personal poor money management skills, low incomes in the job, absence of financial education to create saving awareness, low interest rate provided by financial institutions, lack of trust of employees in the FIs due to financial crisis, low interest rate earned by FIs, high bureaucracy and complex nature of services provided by FIs highly affected employees saving practice in FIs